2019
DOI: 10.1038/s41598-019-49707-8
|View full text |Cite
|
Sign up to set email alerts
|

TBK1 Limits mTORC1 by Promoting Phosphorylation of Raptor Ser877

Abstract: While best known for its role in the innate immune system, the TANK-binding kinase 1 (TBK1) is now known to play a role in modulating cellular growth and autophagy. One of the major ways that TBK1 accomplishes this task is by modulating the mechanistic Target of Rapamycin (mTOR), a master regulator that when activated promotes cell growth and inhibits autophagy. However, whether TBK1 promotes or inhibits mTOR activity is highly cell type and context dependent. To further understand the mechanism whereby TBK1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…YAP1 was an interacting partner of TBK1 (Figure 2A; Figure S2C). These observations were consistent with recent studies suggesting TBK1 may regulate YAP1 and the mTOR substrate S6K (Cooper et al, 2017;Wang et al, 2017;Zhang et al, 2017;Eskiocak et al, 2017;Kim et al, 2013;Antonia et al, 2019;Martin et al, 2014). Pathogen exposure formed TBK1/ mTOR complexes and suppressed TBK1/YAP1 complexes (Figures 2H and 4A).…”
Section: Pkr Phosphorylates Mst1 To Regulate Hippo Signalingsupporting
confidence: 93%
“…YAP1 was an interacting partner of TBK1 (Figure 2A; Figure S2C). These observations were consistent with recent studies suggesting TBK1 may regulate YAP1 and the mTOR substrate S6K (Cooper et al, 2017;Wang et al, 2017;Zhang et al, 2017;Eskiocak et al, 2017;Kim et al, 2013;Antonia et al, 2019;Martin et al, 2014). Pathogen exposure formed TBK1/ mTOR complexes and suppressed TBK1/YAP1 complexes (Figures 2H and 4A).…”
Section: Pkr Phosphorylates Mst1 To Regulate Hippo Signalingsupporting
confidence: 93%
“…Furthermore, autophagy abolition through the ATG5/7 re-sensitized EC109/CDDP knockdown or the use of pharmacological inhibitors is greatly significant [ 36 ] not only in the esophageal, but also in gastric [ 37 ], colorectal [ 38 , 39 ], bladder [ 40 ], ovarian [ 41 ], and prostate cancers [ 42 ]. With regard to TBK1, it has been proven that TBK1 takes part in modulating cell growth and autophagy [ 43 ]. Moreover, Sarraf et al [ 44 ] also indicated that TBK1 exerted an important role in mitophagy.…”
Section: Discussionmentioning
confidence: 99%
“…In response to LPS, TBK1 can directly activate mTORC1, but this function of TBK1 has been controversial ( 29 , 30 ). Therefore, we checked the expression of downstream target proteins of mTORC1 in the placental tissues of control, vehicle-, and amlexanox-treated LPS mice.…”
Section: Resultsmentioning
confidence: 99%